PRE-PROSTHETIC AND PRE-IMPLANT THERAPEUTIC MANAGEMENT OF EDENTULOUS PATIENTS TO IMPROVE BIOMECHANICAL STABILITY OF FUTURE HYBRID PROSTHESES - Gholamreza Shokraei; Agop-Forna Doriana; Forna Norina Consuela (Romanian Society of Oral Rehabilitation, 2024)
The aim of our study was to assess the need for pre-prosthetic and pre-implant therapeutic management of the edentulism complications to impair the biomechanical stability of the future hybrid prostheses. Materials and Method. 150 subjects with partial extended or complete edentulism (mean age 61,54 +/- 8,99 yrs.), eligible for hybrid prosthetic therapy were assessed in Clinical Learning Base of Faculty of Dental Medicine, U.M.F. "Grigore T.Popa" Iasi.. Patients were divided in two groups: Group A (n=96): patients with partial reduced or extended edentulism that were eligible to hybrid prosthetic therapy, retained by fixed teeth-supported prosthetic restoration; Group B (H-PFR/IP) (n=54): patients with total or subtotal edentulism that were eligible to implant-supported hybrid prosthetic therapy, retained by fixed implant-supported prosthetic restorations. The need for non-surgical and surgical procedures in the pro-prosthetic and pro-implant stage was assessed at global level as well as related to the patients' variables within each study group. Results. Significantly higher percentage of patients in Group B requested alveoloplasty (77,8%), alveolar bone addition (83,3%), frenectomy (22,8%), and complex therapy of the temporo-mandibular disorders (94,4%), when compared to Group A (20.8%, 49,0%, 54,2%, respectively) (p <0.001**). Conclusions. Most patients with subtotal or complete edentulism need pre-implant therapeutic interventions (alveoloplasty, alveolar bone addition, frenectomy, and/or treatment of the temporo-mandibular disorders) for the improvement of the biomechanical stability of the future hybrid prostheses. The need for these procedures in the pre-prosthetic stage was significantly lower for patients with extended partial edentulism eligible for removable dentures retained by fixed implant-supported bridges.